How Perceived Organizational Support Effect Employee Commitment Moderated By Work Duration Among Employee In Travel Industries - Anindita, Rina; Michael, Putra; Triana Pratiwi, Mirna; Roespinoedji, Roeshartono (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the current study is to examine the training effect on employee commitment; and to examine the effect of compensation, perceived organizational support on employee commitment moderated by employees’ work duration. The sample of the current study is 120 respondents that consist of employees of travel agency industries. The method applied in the current study is multiple regression analysis method. The result shows that the employees with longer work duration will strengthen the correlation between compensation and commitment; whereas the longer work duration is neither strengthen nor weaken the correlation between perceived organizational support and employee commitment.